Time-restricted feeding and brisk walking in overweight and obese adults - Fadhadli, Fawwaz; Aung, Sanda; Mohd. Noor, Noriah; Razali, Ailin (Fakulti Perubatan dan Sains Kesihatan, UPM, 2021)
Introduction: Obesity and its associated metabolic consequences such as hypertension, type 2 diabetes mellitus and cardiovascular disease are a global epidemic. Conventional treatment of obesity is daily calorie restriction which many patients find challenging. Time-restricted feeding (TRF) is an emerging alternative although very limited scientific evidence is available. Alternatively, brisk walking (BW) has been shown to reduce mortality risks. The objective of this study was to examine the effects of TRF (16 hour/day of fasting) and investigate the additional effects of BW with TRF (16 hour/day of fasting) in overweight and obesity management. Methods: Thirty-six (n=36) overweight and obese participants were enrolled equally into three different groups according to their preferences in this 16- week prospective experimental study; Group A (TRF combined with BW), Group B (TRF alone) and Group C (control group maintaining their lifestyle). Data collection was conducted at the beginning and end of the study for statistical analysis. Results: All Group A and Group B participants showed significant reductions in body mass index, waist circumference, hip circumference, waist-to-hip ratio, body fat percentage, visceral fat level, whole body subcutaneous fat percentage, trunk subcutaneous percentage, legs subcutaneous percentage and arms subcutaneous fat percentage as compared to their control counterparts (Group C) (all p<0.05). However, no significant differences were observed in all anthropometric measurements of Group A participants compared to Group B counterparts. Conclusion: TRF (16 hour/day fasting) can be adopted in weight reduction management of overweight and obese patients. BW for 16 weeks combined with TRF renders no additional effects in overweight and obesity management.